2022
DOI: 10.1001/jamaoto.2021.4549
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Burden of Thyroid Cancer Among the European Union 15+ Countries, 1990-2019

Abstract: ImportanceThe global incidence of thyroid cancer has been increasing rapidly, and this increase has had an attendant burden on health systems. However, it is unclear how the burden of this disease differs among the pre-2004 countries of the European Union (Austria, Belgium, Denmark, Finland, France, Germany, Greece, Ireland, Italy, Luxembourg, Netherlands, Portugal, Spain, Sweden, and the UK), US, Australia, Canada, and Norway (EU15+).ObjectiveTo assess the trends in mortality, incidence, and disability-adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 42 publications
0
20
0
1
Order By: Relevance
“…The trend of rising incidence began to regress first in South Korea in 2014 with a 30% reduction in nodule detection in response to less screening, and as a result, less diagnosis ( 15 ). Similarly, recent findings from the Global Burden of Disease Study found that incidence rates have started to plateau in EU15+ nations and in the US between 2011 and 2019 ( 18 ). However, in low- and middle-income countries, incidence rates have continued to rise ( 19 ).…”
Section: Global Burden Of Thyroid Nodulesmentioning
confidence: 80%
See 2 more Smart Citations
“…The trend of rising incidence began to regress first in South Korea in 2014 with a 30% reduction in nodule detection in response to less screening, and as a result, less diagnosis ( 15 ). Similarly, recent findings from the Global Burden of Disease Study found that incidence rates have started to plateau in EU15+ nations and in the US between 2011 and 2019 ( 18 ). However, in low- and middle-income countries, incidence rates have continued to rise ( 19 ).…”
Section: Global Burden Of Thyroid Nodulesmentioning
confidence: 80%
“…One potential driver is clinical concern that the risk of malignancy for pathologically analyzed samples is underestimated ( 50 ). Although thyroid cancer incidence rates have started to plateau in the US after changes in ATA recommendations, disability-adjusted life years have not yet improved which may reflect suboptimal risk stratification and higher average healthcare expenditures relative to other countries ( 18 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the researchers' conclusions, the trend toward a decrease in incidence and mortality rates has emerged in all countries except for the United States of America, Australia, and Denmark [11].…”
Section: Discussionmentioning
confidence: 99%
“…Eine kürzlich veröffentlichte Erhebung zu Inzidenz, Mortalität und krankheitsbelasteten Lebensjahren in Zusammenhang mit Schilddrüsenkrebs zwischen 1990 und 2019 in Europa, Australien, den USA und Kanada ergab bei gleichbleibenden Inzidenzen in den meisten Ländern eine Abnahme der Mortalität und Krankheitslast im Beobachtungszeitraum. Nur in den USA, Dänemark und Australien waren sowohl altersadjustiert steigende Todesraten als auch krankheitsbelastete Lebensjahre zu beobachten 1 .…”
Section: Epidemiologieunclassified